2016
DOI: 10.1186/s13027-016-0090-9
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of high risk human papilloma viruses in women treated with antiretroviral and in healthy controls and discordance with cervical dysplasia in the South of Benin

Abstract: BackgroundHigh risk oncologic Human Papilloma Virus (HPV) is one of the leading causes of cervical cancer worldwide. We investigated HPV genotypes among women living or not with Human Immuno-deficiency Virus (HIV) in two major hospitals in the south of the republic of BENIN in the city of Cotonou. Our objective is to investigate the association of high risk-HPV to cervical dysplasia among women under stringent anti-retroviral (ARV) treatment and in controls without HIV.MethodsThe investigation was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…The included studies comprise of review articles which made the bulk of the articles with 77.7% (7/9) [90][91][92][93][94][95][96] and (1/9) transversal case control study [97] and (1/9) quantitative study [98] and each contributed 11.1% respectively.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies comprise of review articles which made the bulk of the articles with 77.7% (7/9) [90][91][92][93][94][95][96] and (1/9) transversal case control study [97] and (1/9) quantitative study [98] and each contributed 11.1% respectively.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The studies were done and reviewed from different study settings. About 11.1% (1/9) study generalized about SSA with no specific country mentioned [90], 44% (4/9) reported about Uganda [91,92,95,96], 33% (3/9) South Africa (SA) [93,95,96], 22% (2/9) Senegal [94,96], (1/9) Zambia [93], (1/9) Nigeria [98], and (1/9) Benin [97], and each contributed 11% respectively. Among the included studies, only three were conducted in an urban setting; those of the rest of the studies were not mentioned.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations